Manajemen Akademik: Konsep, Tujuan, dan Fungsi dalam Meningkatkan Kualitas Pendidikan - Dahrani, Dahrani; busra, Aminudin; Rizadiliyawati, Rizadiliyawati; Syaifuddin, Muhammad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Academic management plays a strategic role in improving the quality of education by focusing on curriculum management, human resource development, and the utilization of technology. Effective curriculum management ensures adaptability and relevance to the needs of students, society, and the job market. Human resource development, through continuous professional training, enhances the competencies of educators and administrative staff, fostering an environment of innovation and collaboration. Additionally, the integration of technology in academic management streamlines administrative processes, supports data-driven decision-making, and expands learning accessibility and flexibility for students. However, challenges such as digital divides and infrastructure limitations require inclusive strategies to ensure equitable implementation. This study emphasizes that the synergy between these three components is crucial for creating an educational ecosystem that is efficient, effective, and future-oriented. Academic management, when executed effectively, serves as the foundation for producing competent, innovative, and globally competitive graduates.